2013
DOI: 10.3390/rs5041998
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Spatial Domain Size on the Performance of the Ts-VI Triangle Method in Terrestrial Evapotranspiration Estimation

Abstract: This study aims to investigate the impact of the spatial size of the study domain on the performance of the triangle method using progressively smaller domains and Moderate Resolution Imaging Spectroradiometer (MODIS) observations in the Heihe River basin located in the arid region of northwestern China. Data from 10 clear-sky days during the growing season from April to September 2009 were used. Results show that different dry/wet edges in the surface temperature-vegetation index space directly led to the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Traditionally, traditional TIMs are only applicable to homogeneous surfaces (Carlson, 2007;Petropoulos et al, 2009;Zhang, 2009). Moreover, a recent study from Tian et al (2013) indicated that the variation of the spatial domain size would directly lead to the deviation of ET estimates. This created difficulty for traditional TIMs to couple with other pixel-based models.…”
Section: Advantages Of Etemlmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, traditional TIMs are only applicable to homogeneous surfaces (Carlson, 2007;Petropoulos et al, 2009;Zhang, 2009). Moreover, a recent study from Tian et al (2013) indicated that the variation of the spatial domain size would directly lead to the deviation of ET estimates. This created difficulty for traditional TIMs to couple with other pixel-based models.…”
Section: Advantages Of Etemlmentioning
confidence: 99%
“…(4) It is difficult to couple TIMS with other models. Tian et al (2013) indicated that different dry/wet edges determined in the VFC/LST trapezoid space directly led to the deviation of ET estimates due to the variation of the spatial domain size. This domain-dependent problem led to difficulty with this type of model being coupled with other pixel-based models.…”
Section: Introductionmentioning
confidence: 99%
“…• empirical methods that involve the use of statistically-derived relationships between ET and vegetation indices such as the normalized difference vegetation index (NDVI) or the enhanced vegetation index (EVI) [20][21][22][23][24][25], • residual methods of surface energy balance (single-and dual-source models) [8,26] which include the Surface Energy Balance Algorithm over Land (SEBAL) [27,28], Surface Energy Balance System (SEBS) [8,29,30] and Mapping EvapoTranspiration at high Resolution with Internalized Calibration (METRIC) [6,31,32], • physically-based methods that involve the application of the combination of Penman-Monteith [7,33,34] and Priestley-Taylor types of equations [35][36][37][38][39], and • Data assimilation methods adjoined to the heat diffusion equation [40] and through the radiometric surface temperature sequences [41].…”
mentioning
confidence: 99%
“…The typical definition of drought is a period with a precipitation deficit that influences agriculture, water resources, incorporating air temperature, enhancing dry/wet edge determination, combining with thermal inertia, etc. [23,24,31,35,36]. The factors that most affect the accuracy of the TVDI were determined and evaluated when the TVDI was used to estimate water deficits [37].…”
Section: Introductionmentioning
confidence: 99%